Co-Occurring Psychiatric and Substance Use Disorders: Clinical Survey Among a Rural Cohort of Italian Patients - Milano G (Dove Medical Press, 2019)
Giulia Milano,1,* Hayley M Vergani,1,* Simone Cattedra,1 Roberto Carrozzino,2 Francesca Mattioli,1 Luigi Robbiano,1 Antonietta Martelli1 1Department of Internal Medicine, Clinical Pharmacology and Toxicology Unit, University of Genoa, Genoa, Italy; 2Department of Addiction, Health Service ASL2 Savonese, Savona, Italy*These authors contributed equally to this workCorrespondence: Hayley M VerganiDepartment of Internal Medicine, Clinical Pharmacology and Toxicology Unit, University of Genoa, Viale Benedetto XV, 2, Genoa I-16132, ItalyTel +39 0103538850Fax +39 0103538232Email hayley.vergani@gmail.comPurpose: Dual diagnosis (DD) is the co-occurrence of both a mental illness and a substance use disorder (SUD). Lots of studies have analysed the integrated clinical approach, which involves both psychiatry and toxicology medical experts. The purpose of this study is to analyse the socio-demographic characteristics and treatment strategies of patients with DD in a rural area of Italy.Patients and Methods: Clinical data of 750 patients were collected in 2016 through the analysis of health plan records.Results: The rate of co-occurring disorders is highly variable among people with SUD. In the considered area, patients with DD are 24%, of these only 46.1% have been treated with an integrated clinical program. Moreover, this percentage is further reduced (35.8%) if only patients with heroin use disorder are considered.Conclusion: A comprehensive revision of DD treatment is needed, especially for people suffering from heroin use disorder and living in remote areas. Meticulous data analysis from other addiction health services of rural areas could be necessary to identify a science-based clinical intervention.Keywords: dual diagnosis, integrated treatments, substance use disorder, social stigma, rural populations